2013
DOI: 10.1063/1.4789865
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of double emulsion droplet in shear flow

Abstract: Hydrodynamic behaviors of double emulsion droplets in shear flow, both deformation and breakup, are investigated numerically. We find that the inner drop is deformed in a uniform vortical flow interior to the outer drop under steady state deformation conditions and provides an additional deformation resistance for the integral droplet especially when its volume fraction is large. In particular, we report four types of breakup modes via three mechanisms (i.e., necking, end pinching, and capillary instability), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(62 citation statements)
references
References 27 publications
2
60
0
Order By: Relevance
“…The dynamics of double emulsion droplets and their break-up mechanism are not well understood (Chen, Liu, & Shi, 2013), therefore it is expected that the scaling relations derived by Nazir, Boom, and Schroën (2013) may not hold. In the present work, we first have briefly discussed the effects of some of the process parameters individually, and compiled the results into a dimensionless plot from which conclusions regarding droplet break-up mechanisms were made.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The dynamics of double emulsion droplets and their break-up mechanism are not well understood (Chen, Liu, & Shi, 2013), therefore it is expected that the scaling relations derived by Nazir, Boom, and Schroën (2013) may not hold. In the present work, we first have briefly discussed the effects of some of the process parameters individually, and compiled the results into a dimensionless plot from which conclusions regarding droplet break-up mechanisms were made.…”
Section: Resultsmentioning
confidence: 97%
“…In some cases, the droplet to pore size ratios obtained in our work were significantly higher than those reported for single emulsions. This is attributed to the deformation resistance of highly viscous dispersed phase (W/O) in our system (Chen et al, 2013), which has led to less effective droplet break-up. Compared to many other premix membrane emulsification studies focused on double emulsions, the size reductions we obtained are at the lower end of the reported range of 0.2-3.5 (Shima et al, 2004;Surh, Vladisavljević, Mun, & McClements, 2007;Vladisavljević et al, 2004;Vladisavljević et al, 2006), which shows the effectiveness of the packed bed system in breaking up the double emulsion droplets.…”
Section: Droplet Break-up Mechanismmentioning
confidence: 95%
“…The VOF method coupled with CSF (continuum surface force) (Brackbill et al, 1992) approach was found to be very successful in predicting droplet formation and break up (Chen et al, 2013b;Vladisavljević et al, 2014;Zhang, 1999), droplet deformation (Chen et al, 2013a) and dripping to jetting transitions (Chen et al, 2013b;Herrada et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…fractal, latent heat storage, metal foam, solidification 1 | INTRODUCTION Latent heat storage (LHS) based on a phase change material (PCM) is found in a multitude of practical engineering applications, such as solar energy utilization, 1 building energy conservation, 2 battery module cooling, 3 chemical engineering, 4,5 and space thermal control. 6 In these applications, the energy charging and discharging rate are of great significance, so the challenge is enhancing the thermal performance of engineering-utilized PCMs arising from their low thermal conductivity.…”
Section: Discussionmentioning
confidence: 99%